Prospective study on the impact of BEAM versus FEAM conditioning on occurrence of neutropenic enterocolitis and on transplant outcome in lymphoma patients - Benedetti, Edoardo; Traverso, Ginevra; Pucci, Giulia; Morganti, Riccardo; Bramanti, Emilia; Cavallo, Federica; Capochiani, Enrico; De Maria, Maurizio; Ricchiuto, Vittorio; Stella, Massimo Salvatore; Galimberti, Sara (Frontiers in Oncology, 2024)
Introduction Carmustine (BCNU), etoposide, cytarabine, and melphalan (BEAM) are a widely used high-dose chemotherapy regimen for autologous stem cell transplantation transplant (ASCT) in lymphoid malignancies. During BCNU shortages, some centers switched to fotemustine-substituted BEAM (FEAM). Neutropenic enterocolitis (NEC) is a life-threatening complication occurring after intestinal mucosa damage related to intensive chemotherapy. NEC mortality may be up to 30%–50%. In our study, we compared NEC incidence, symptoms, mortality, and transplant outcome in terms of overall survival (OS) and progression-free survival (PFS) in the BEAM vs. FEAM groups. Furthermore, we compared the cost of hospitalization of patients who did vs. patients who did not experience a NEC episode (NECe). Methods A total of 191 patients were enrolled in this study (N = 129 and N = 62 were conditioned with BEAM and FEAM, respectively). All patients received bed-side high-resolution ultrasound (US) for NEC diagnosis. Results and discussion NEC incidence and NEC-related mortality were similar in the BEAM and FEAM groups (31% and 40.3%, p = 0.653, and 5% and 8%, p = 0.627, respectively). At a median follow-up of 116 months, no difference was noted between BEAM vs. FEAM groups in terms of OS and PFS (p = 0.181 and p = 0.978, respectively). BEAM appeared equivalent to FEAM in terms of NEC incidence and efficacy. The high incidence of NEC and the low mortality is related to a timely US diagnosis and prompt treatment. US knowledge in NEC diagnosis allows to have comparable days of hospitalization of patients NECpos vs. patients NECneg. The cost analysis of NECpos vs. NECneg has been also performed.